Negotiations on the Iranian nuclear program: Phenomenon of the JCPOA, current status, and prospects - S. S. Shestakova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2025)
The growing instability and conflict in contemporary world politics result in the further erosion of international regimes, particularly those of nuclear nonproliferation. A vivid illustration of this trend is the deepening crisis over Iran’s nuclear program (INP), which not only undermines international security but also acquires a special regional dimension against the backdrop of the escalating Palestinian-Israeli conflict. This context, as well as the pending deadline for the review of Iran’s nuclear dossier in the UN Security Council, makes the study of the  nature and content of the diplomatic efforts aimed at a peaceful settlement of the situation around the INP particularly relevant. This article identifies the specific features of the INP negotiation process, its core principles, and mechanisms, and examines the problems and prospects of further developments around the INP under the current conditions. Building on the neo-institutional approach to international studies, the author concludes that the Joint Comprehensive Plan of Action (JCPOA) should be considered an element of a unique negotiation system that encompasses a range of formal and informal norms and practices and can be generally denoted as ‘JCPOA spirit’. However, this system fell into a crisis shortly after the Iran nuclear deal was approved. This article delves into the problems that have effectively led the INP negotiations to an impasse. The author concludes that the lack of progress in resolving the situation around the INP at the current stage is attributed to a number of factors, including the politicization of the negotiation process, the credibility gap between its parties, the reenactment of sanctions against Iran and the introduction of additional demands by the latter on the U.S. and the E3 countries, as well as the breach of the INP specifications and the ‘Israeli’ factor. In this context, the author outlines three scenarios for the developments around Iran’s nuclear dossier given the prospects of the Iran nuclear deal: restoration of the JCPOA in its original form, its partial revision, or failure to revive the arrangement. The author argues that given the unfavorable international political environment, the situation around the JCPOA will develop under the third scenario in the short run.